A quantum chemistry study of curvature effects on boron nitride nanotubes/nanosheets for gas adsorption. Issue 29 (11th July 2016) - Sha, Haoyan; Faller, Roland
Abstract : Various boron nitride sheets interacting with noble gases, oxygen, and water on both sides of the surface were studied using high level DFT. Abstract : Quantum chemistry calculations were performed to investigate the effect of the surface curvature of a Boron Nitride (BN) nanotube/nanosheet on gas adsorption. Curved boron nitride layers with different curvatures interacting with a number of different gases including noble gases, oxygen, and water on both their convex and concave sides of the surface were studied using density functional theory (DFT) with a high level dispersion corrected functional. Potential energy surfaces of the gas molecules interacting with the selected BN surfaces were investigated. In addition, the charge distribution and electrostatic potential contour of the selected BN surfaces are discussed. The results reveal how the curvature of the BN surfaces affects gas adsorption. In particular, small curvatures lead to a slight difference in the physisorption energy, while large curvatures present distinct potential energy surfaces, especially for the short-range repulsion.